The creepy line [videorecording (DVD)] - Taylor, M. A.; Taylor, M. A.; Peterson, Jordan B; Epstein, Robert (Janson Media, 2019)
An eye-opening documentary, reveals the stunning degree to which society is manipulated by Google and Facebook and blows the lid off the remarkably subtle, hence powerful, manner in which they do it. A title culled from the words of former Google CEO Eric Schmidt, when during a 2010 interview he explained Googles code of conduct, The Google policy on a lot of things is to get right up to the creepy line and not cross it.